Isolation, Identification and Molecular Characterization of Thermophilic Bacteria from Soil and Water of Khurmal Spring - Khasraw, Kozhi; Ghafoor, Dlzar D. (Sulaimani Journal for Pure and Applied Sciences, 2019)
Thermophilic bacteria are regarded as a key source of thermostable enzymes that are of great industrial importance. The present study was conducted to identify and characterize the thermophilic bacteria isolated from Khurmal spring in Sulaimaniyah, Kurdistan region of Iraq. Water and soil samples from different sites were collected used to isolate thermophilic bacteria. Seven different isolates of Bacillus (5 from water and 2 from soil) were characterized for their biochemical properties. Activity of different enzymes (catalase, amylase, cellulose, protease, and esterase) was measured for each isolate. The bacterium with the ability to tolerate high temperatures was identified as Bacillus sp. both by using phenotypic and genotypic methods including microscopic characterization, Gram staining and 16S rRNA sequencing. BLAST search analysis of the sequence showed maximum identity with different Bacillus sp. with similarities in the range of (95-98%). The study confirmed that the isolated Bacillus sp. to be a true thermophile and could be a source of thermostable enzyme which can be exploited for pharmaceutical and industrials applications.
Keywords: MRSA; cefoxitin; polymerase chain reaction; Saureus